The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5296/ijl.v4i4.2228
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Context on the Iranian EFL Learners’ Idiom Retention

Abstract: Idioms, forms of figurative language, are used pervasively in both spoken and written discourse. However, mainly due to their figurative nature, they are often considered difficult to learn. The present study tried to first of all briefly investigate the language learners' attitudes toward learning L2 idioms. It then compared the effect of written vs. video-graphic contexts on the language learners' long-term and short-term retention of idioms. To know about the language learners' attitudes to learning English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(12 reference statements)
1
0
0
Order By: Relevance
“…As represented in the table, a mean score of 3.47 (SD = .862) was given to the statement "I can easily remember many idioms by remembering the short films", which indeed reflects the effect of context on the language learners" retention of idioms. This broadly supports the work of other studies (e.g., Chun & Plass, 1996;Khonbi & Sadeghi, 2017;Neissari et al, 2017;Rohani, Ketabi, & Tavakoli, 2012;Tabatabaei & Gahroei, 2011;Vasiljevic, 2015) which showed that when idioms presented through films and movie clips, better retention and intake is achievable. Another relatively high mean score (M = 3.69, SD = .604) was given to the students" positive perceptions toward the usefulness of short films in learning English idioms independently.…”
Section: Participants' Attitudessupporting
confidence: 90%
“…As represented in the table, a mean score of 3.47 (SD = .862) was given to the statement "I can easily remember many idioms by remembering the short films", which indeed reflects the effect of context on the language learners" retention of idioms. This broadly supports the work of other studies (e.g., Chun & Plass, 1996;Khonbi & Sadeghi, 2017;Neissari et al, 2017;Rohani, Ketabi, & Tavakoli, 2012;Tabatabaei & Gahroei, 2011;Vasiljevic, 2015) which showed that when idioms presented through films and movie clips, better retention and intake is achievable. Another relatively high mean score (M = 3.69, SD = .604) was given to the students" positive perceptions toward the usefulness of short films in learning English idioms independently.…”
Section: Participants' Attitudessupporting
confidence: 90%